2020
DOI: 10.1177/1071100719898279
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Experience With SPECT/CT to Evaluate Periarticular Arthritis Progression and the Relationship With Clinical Outcome Following Ankle Arthrodesis

Abstract: Background: Single photon emission computed tomography combined with computed tomography (SPECT/CT) could potentially aid in diagnosing periarticular arthritis/activity and progression, facilitate effective treatment options, and evaluate the effect surgery has on the clinical outcome of patients with ankle arthritis. The goal of our study was to assess SPECT/CT activity in the ankle and periarticular joints before and after ankle fusion surgery and determine whether it was associated with clinical pain and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…7 Interestingly, in contrast to the same study listed above, this systematic review found that TNJ joints had the highest CT-confirmed union rates at 90% whereas they found TNJ joints had the worst fusion among joints at 79.6%. 7 CT provides the practitioner an indepth 3-dimensional analysis of the fused joint allowing for All patients 1,3-5,10-14, [16][17][18][19][20]24,26,28,31,33,35,37,39,41,42 1015 0.79 0.70 0.88 11.99 -91.81 All joints 1,[3][4][5][9][10][11]13,14,16,18,19,[26][27][28]31,35,37,41,42 1301 0.83 0.73 0.93 9.00 -100.07 Ankles 3,5,17,18,32,37 237 0.86 0.73 0.98 1.61 -209.70 TTC 1,3,4,14,16,…”
Section: Discussionmentioning
confidence: 99%
“…7 Interestingly, in contrast to the same study listed above, this systematic review found that TNJ joints had the highest CT-confirmed union rates at 90% whereas they found TNJ joints had the worst fusion among joints at 79.6%. 7 CT provides the practitioner an indepth 3-dimensional analysis of the fused joint allowing for All patients 1,3-5,10-14, [16][17][18][19][20]24,26,28,31,33,35,37,39,41,42 1015 0.79 0.70 0.88 11.99 -91.81 All joints 1,[3][4][5][9][10][11]13,14,16,18,19,[26][27][28]31,35,37,41,42 1301 0.83 0.73 0.93 9.00 -100.07 Ankles 3,5,17,18,32,37 237 0.86 0.73 0.98 1.61 -209.70 TTC 1,3,4,14,16,…”
Section: Discussionmentioning
confidence: 99%